Thermodynamic Equilibrium of Hydrate Formation in Multiphase and Multicomponent Systems - Isabela T. Hilario; Reginaldo Guirardello (Chemical Engineering Transactions, 2024)
Hydrates are crystalline structures composed of water molecules and low molecular weight compounds, formed under appropriate conditions of pressure and temperature. Depending on the circumstances, these crystalline solids can be seen as a problem or a solution. In a negative context, gas hydrates tend to cause serious flow assurance problems in the petroleum industry. On the other hand, these hydrates can be used in the separation, transport and storage of gas, playing an important role in reducing the impacts caused by greenhouse gases (GHG). In this context, there is a need for a consistent assessment of the thermodynamic equilibrium of systems with a tendency to form hydrates in order to solve the problems and enable their large-scale use. Therefore, this study presents a rigorous analysis of hydrate phase equilibrium in systems composed of carbon dioxide (CO2), methane (CH4), propane (C3H8) and glycerol (C3H8O3). For this, the isofugacity and Gibbs energy minimization methodologies were used. With this work, it was possible to develop a rigorous evaluation of the phase equilibrium of hydrate-forming systems, investigate the use of C3H8 as a promoter and C3H8O3 as a hydrate inhibitor, and the influence of thermodynamic conditions on the occupation of hydrate cavities by molecules CO2 and CH4. The results obtained in this study were compared with experimental data available in the literature, enabling the conclusion about the satisfactory prediction of the phase equilibrium behavior of the investigated systems.